Simulated Performance of SCTP and TFRC Over MANETs: The Impact of Traffic Load and Nodes Mobility - Kanellopoulos, Dimitris N; Wheeb, Ali H (International journal of business data communications and networking, 2020)
Mobile ad-hoc networks (MANETs) are composed of mobile nodes communicating through wireless medium, without any fixed centralized infrastructure. Providing quality of service (QoS) support to multimedia streaming applications over MANETs is vital. This paper focuses on QoS support, provided by the stream control transmission protocol (SCTP) and the TCP-friendly rate control (TFRC) protocol to multimedia streaming applications over MANETs. In this study, three QoS parameters were considered jointly: (1) packet delivery ratio (PDR), (2) end-to-end delay, (3) and throughput. Specifically, the authors analyzed and compared the simulated performance of the SCTP and TFRC transport protocols for delivering multimedia streaming over MANETs. Two simulation scenarios were conducted to study the impact of traffic load and node speed (mobility) to their performance. Based on the simulation results, the authors found that the PDR and the end-to-end delay of TFRC are slightly better than those of SCTP in both scenarios. Additionally, the performance of SCTP is significantly better than TFRC in terms of throughput.